Cartilage erosion in laryngeal and hypopharyngeal cancer correlation between radiology and histopathology - Kathar, Mohamed Abdul; Michael, Rajiv C.; Shyam, Aparna; Mukhopadhyay, Sramana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The aim of this study was to assess the accuracy of preoperative contrast enhanced computed tomography (CECT) of neck with or without magnetic resonance imaging (MRI) in determining cartilage erosion in patients with laryngeal and hypo pharyngeal cancers and correlate this with the final histopathology report (HPE). Methods: Forty patients diagnosed clinically with stage 3 laryngeal and hypo pharyngeal cancer were subjected to flexible laryngoscopy and CECT of neck. Patients with doubtful cartilage erosion on CECT were subjected to additional MRI. Radiologic findings including cartilage sclerosis, invasion and penetration on CECT and MRI were then correlated with HPE in patients who underwent total laryngectomy. Results: CECT scan showed cartilage invasion in 30 cases. There were ten patients with doubtful cartilage erosion on the CECT scan who were then subjected to additional limited MRI which was compared with CECT scan and operative findings. Thyroid cartilage erosion was confirmed on MRI in five of the ten cases where CECT scan findings were equivocal. CECT scan failed to predict cricoid and arytenoid cartilage invasion in five cases and six cases respectively. Though MRI was a problem-solving tool, it had one false positive result. Conclusions: CECT scan helped to identify cartilage erosion in 91.3% of cases which immensely contributed to the staging and treatment planning of laryngeal and hypo pharyngeal cancers. When findings on CECT are equivocal, the addition of MRI improves the accuracy of detecting cartilage involvement.